Antioxidant Properties and Thermal Stability of Active Packaging Incorporated with Dyes - Wahyu Dewanti Erika; Tarman Kustiariyah; Santoso Joko; Nurjanah; Dyah Hardiningtyas Safrina; Berlyanto Sedayu Bakti; Nurbaya Sari Rodiah; Fateha (BIO Web of Conferences)
Marine polysaccharides-based packaging that is both bio-based and biodegradable has garnered significant interest for preserving food freshness. This study introduces an eco-friendly packaging solution derived from agar and chitosan, designed not only to protect food but also to serve as an innovative indicator of rancidity and spoilage. By blending agar and chitosan using casting methods and mixed with various dyes, a material was created that demonstrated excellent compatibility due to their structural similarities and the thermal stability, confirmed by TGA and DSC analysis. TGA and DSC examinations verified the thermal stability of the blends at 180°C, with low crystallinity. Furthermore, agar and chitosan-based film with added 0.2% BTB dye possesses 493 ppm of DPPH scavenging activity while the control sample retains on 776.03 ppm. These results offer significant insights into the potential industrial applications of these compounds, particularly in sectors where both high thermal stability and effective antioxidant properties are crucial.